miR-146b level and variants is associated with endometriosis related macrophages phenotype and plays a pivotal role in the endometriotic pain symptom - Zengzhen Zhang; Huiqing Li; Zhitao Zhao; Baofeng Gao; Li Meng; Xianguang Feng (Elsevier, 2019)
Objective: The aim of this study was to explore the effect of miR-146b expression and variants on endometriosis and its associated pain symptom. Materials and methods: Genotyping and expression of miR-146b was performed on 74 endometriosis patients and 23 healthy controls. ESCs were subsequently co-cultured with peripheral blood (PB)-derived monocytes (PBMC)-driven macrophages. After overexpression and inhibition of miR-146b, cytokine production from the macrophages were determined by enzyme-linked immunosorbent assay (ELISA). Western blot were done to measure the regulation of IRF5 by miR-146b. Results: We found that miR-146b expression was increased in PF supernatant and PF CD14 + monocytes/Macrophages of endometriosis patients, with endometriosis patients with pain (EPWP) showing higher miR-146b expression compared with the endometriosis patients without pain (EPNP). CT/CC genotype of miR-146b rs1536309 was associated with the risk of pain symptom of endometriosis. For the function studies, we found that miR-146b was involved in the negative regulation of inflammation through attenuating IRF5 expression. Macrophages from patients who carries CT/CC genotype of miR-146b rs1536309 showed decreasing miR-146b expression and enhancement of the ability of pro-inflammation. Conclusions: Our findings suggest an important role of miR-146b level and variants in endometriosis that helps to regulate the process of endometriosis and its associated pain. Keywords: Endometriosis, microRNA, Macrophage, Polymorphism, Polarization